The stage performance of Peer Gynt in Mysore: is 'global Ibsen' against globalization? - Huq, Sabiha (Nordlit, 2015)
This article discusses an adaptation of Peer Gynt in the Kannada language, which was staged in the state of Karnataka, India in 1995. The director of the play asserted his concern of Western notion of interculturalism that is inevitably affected by the process of economic globalization, and according to him India has a different situation as there is ‘tremendous resistance’ to the homogenizing, commoditizing, and anti-democratic tendencies of globalization. Popular terms like ‘technology transfers’, ‘free trade’, ‘democracy’ etc., that are connected with globalization are criticized in the production and it is strongly rooted in serious issues like communal conflict and economic exploitation in contemporary India, providing a notion that globalization is a red herring to divert people from local realities. The analysis of the performance text and the images from the stage performance show how the creative forces behind this production were deeply preoccupied with the notion of the global vs. the national.
Keywords: globalization; market economy; Gandhian nationalism.